Recommendations for Sustaining California's Statewide Mental Health Prevention and Early Intervention Programs - Burnam, M. Audrey (RAND Corporation, 2014)
Provides preliminary advice about which of the California Mental Health Services Authority's Prevention and Early Intervention activities seem most valuable to sustain or, in some cases, enhance.